2020
DOI: 10.4236/fns.2020.111002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>γ</i>-Polyglutamic Acid on Blood Glucose and Caecal Short Chain Fatty Acids in Adult Male Mice

Abstract: γ-Polyglutamic acid (γ-PGA) is a major component of Natto. We hypothesized that γ-PGA could reduce postprandial glucose rise and plasma glucose levels. Mice were fed a 0.1% γ-PGA-containing diet or control diet for 91 days. Maltose and starch tolerance tests were performed, and plasma lipids, glucose levels, and caecal short chain fatty acids (SCFAs) were measured. Mice were co-administered γ-PGA and starch to suppress the initial rise in blood glucose levels. Blood glucose levels at 15 min were significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In addition, a hyperglycemia inhibitor that consists primarily of the γ-PGA potassium salt has been patented [10]. Tamura et al also reported that co-administration of γ-PGA suppresses the initial rise in blood glucose levels after starch loading in mice [18]. Therefore, the high-γ-PGA natto-induced suppression of blood glucose elevation in this study might have been affected by γ-PGA, the content of which was markedly different between the high-and low-γ-PGA natto meals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a hyperglycemia inhibitor that consists primarily of the γ-PGA potassium salt has been patented [10]. Tamura et al also reported that co-administration of γ-PGA suppresses the initial rise in blood glucose levels after starch loading in mice [18]. Therefore, the high-γ-PGA natto-induced suppression of blood glucose elevation in this study might have been affected by γ-PGA, the content of which was markedly different between the high-and low-γ-PGA natto meals.…”
Section: Discussionmentioning
confidence: 99%
“…In a human study, it was reported that a single administration of high γ-PGA natto diet lowered postprandial blood glucose level of γ-PGA more than a single administration of low γ-PGA natto diet, ( 11 ) and in a mouse study, oral administration of starch + γ-PGA significantly lowered blood glucose level than starch alone, suggesting a hypoglycemic effect of γ-PGA. ( 24 ) The low blood glucose levels in the NA group are presumably due to the hypoglycemic effect of γ-PGA.…”
Section: Discussionmentioning
confidence: 97%
“…In the animal study by Tamura et al, the inhibitory effect of γ -PGA on the blood glucose levels increased at the initial phase after starch loading [ 17 ]. γ -PGA is a viscous substance [ 3 ], and its content is approximately eight-fold higher in HPGA natto than in LPGA natto.…”
Section: Discussionmentioning
confidence: 99%